Peas and Carrots - Tod Williams; Billie Tsien (Oz, 1996)
The need for shelter is as essential as the need for food. As architects we are committed to provide, and then transcend, the essential need for shelter; and we believe it is equally essential that we do so with thought, compassion and love.